TINJAUAN HUKUM PERAN DESA DALAM IMPLEMENTASI PEMBANGUNAN DI KABUPATEN WAKATOBI - Darmawan Wiridin; Ramadhan (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
Village development is an integral part of sustainable and inclusive national development. In the context of decentralization and regional autonomy, villages are granted significant authority to serve as the driving force for grassroots development. This study discusses the role of villages in implementing development in Wakatobi Regency, focusing on the village government as the subject of development, village authority, village fund management, community empowerment, local economic development, and the relationship between villages and autonomy. The research also examines factors hindering the role of villages in development within Wakatobi Regency, identifying challenges faced by both central and regional governments in implementing village governance policies. The study employs a normative-empirical legal research method with a normative approach to analyze regulations governing the role of villages in development, such as Law No. 6 of 2014 concerning Villages and its implementation.The findings reveal that obstacles to the effective implementation of village roles in development in Wakatobi Regency include limited human resources (HR), low institutional capacity of village governments, weak supervision and community participation, inadequate understanding of village officials regarding regulations governing development, suboptimal utilization of village funds, and the underutilization of the Village Consultative Body (BPD) in conducting oversight